The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fmicb.2018.02314
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Cys-2232 in Clostridioides difficile Toxin B Modulates Receptor Binding

Abstract: Clostridioides difficile toxins TcdA and TcdB are large clostridial glucosyltransferases which are the main pathogenicity factors in C. difficile-associated diseases. Four highly conserved cysteines are present in all large clostridial glucosyltransferases. In this study we focused on the conserved cysteine 2232 within the combined repetitive oligopeptide domain of TcdB from reference strain VPI10463 (clade I). Cysteine 2232 is not present in TcdB from hypervirulent strain R20291 (clade II), where a tyrosine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…The TcdB fragment, referred to by the authors as FZD-binding domain (FBD), covers amino acid residues 1285–1804 and matches nearly exactly the delimitations of the additional receptor-binding domain (residues 1349–1811) discovered previously [26]. Recently, Chung et al have shown that TcdB NAP1 exhibited only weak binding to FZD2 [33]. In line with this observation, the authors showed that a fragment of TcdB VPI covering amino acid residues 1101–1836 (and which largely overlaps with the FBD described above) was capable of competitively inhibiting TcdB VPI but not TcdB NAP1 .…”
Section: Discussionmentioning
confidence: 61%
“…The TcdB fragment, referred to by the authors as FZD-binding domain (FBD), covers amino acid residues 1285–1804 and matches nearly exactly the delimitations of the additional receptor-binding domain (residues 1349–1811) discovered previously [26]. Recently, Chung et al have shown that TcdB NAP1 exhibited only weak binding to FZD2 [33]. In line with this observation, the authors showed that a fragment of TcdB VPI covering amino acid residues 1101–1836 (and which largely overlaps with the FBD described above) was capable of competitively inhibiting TcdB VPI but not TcdB NAP1 .…”
Section: Discussionmentioning
confidence: 61%
“…There is currently no standard nomination for TcdB variants, miscellaneous names referred to same toxin variants were sometimes assigned in different studies. For example, TcdB variant initially identified from NAP1/BI/027 strains was later called TcdB 027 28,29 , TcdB HV 22,30 , TcdB NAP1 15 , TcdB2 31 , TcdB R20291 32,33 , or TcdB-R20291 34 . In 2005, Rupnik et al 35 proposed nomenclature of C. difficile toxin variants by adding the bacterial strain in which the toxin was originally found.…”
Section: Discussionmentioning
confidence: 99%
“…The classical TcdB (TcdB1) uses chondroitin sulfate proteoglycan 4 36 , poliovirus receptor-like 3 37 , and frizzled proteins (FZDs) 38 as cellular receptors; and can glucosylate small GTPase such as RhoA/B/C, Rac1, Cdc42, TC10, TCL, RhoG, Rap, and Ras [39][40][41] . Recent studies showed that TcdB2 only weakly bound to FZDs when compared with TcdB1 32,42 , likely owing to discrepancies between FZD-binding sequences of TcdB1 and TcdB2 43,44 . Also, when compared with TcdB1, both TcdB3 and TcdB4 showed a drastically reduced ability to glucosylate RhoA and Cdc42 15,23 , which was also supported by our sequence analyses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, sequence variations in the toxin genes exist across C. difficile strains and could affect receptor-binding specificity, preferences toward distinct small GTPases, overall toxicity, and antigenicity. For instance, strains such as R20291 (belonging to RT027) produces a TcdB variant with ~8% of residue differences from the reference TcdB, which exhibited a significant impact on its immunogenicity: mice immunized with the reference TcdB developed resistance to the same TcdB, but all died when challenged with this variant TcdB 34 , and several antibodies raised against the reference TcdB, including the FDA approved therapeutic antibody bezlotoxumab, either do not recognize or have lower efficacy against this TcdB variant [34][35][36] . Furthermore, this TcdB variant also loses the ability to recognize frizzled (FZD) proteins, which are one of the major receptors for the reference TcdB, due to residue changes at the FZD-binding interface 35,[37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%